The Structural Relationship Model of Organizational Capability and Corporate Social Responsibility Affecting the Sustainability of the Certified Green Industry in Thailand - Trongwattanawuth, Sirirat; Siriprasertsin, Piyawan (Journal of Humanities and Social Sciences Thonburi University, 2022)
The objective of this research was to study the structural relationship of organizational abilities. and social responsibility affecting the sustainability of the green industry is guaranteed in Thailand. The researcher collected data from 3,387 factory operators who received certificates from level 1 to 5 in 9 green industries related to agricultural products, plants, vegetables, food, seasonings or food preparations, tea and coffee, amounting to 3,387 factories. There were sample sizes of 438 factories. The research instruments were questionnaires and the statistics used were mean, standard deviation. The analysis of the data by using the structural analysis of the relationship between the variables. The results showed that the model was consistent with the empirical data. All values ​​of the straightness test index of the harmonious model were good. The hypothesis test found that organizational capability had a positive direct influence on sustainability with a direct influence = 0.932. It also had a positive indirect influence through corporate social responsibility with a positive indirect influence = 0.392 and a positive total influence = 0.956, and corporate social responsibility with a positive direct influence on sustainability with a positive direct influence = 0.421 and the total influence = 0.421 with a statistically significant level of 0.01 which was consistent with the research hypothesis.